KEBIASAAN MAKANAN IKAN MOTAN, Thynnichthys thynnoides, Bleeker, 1852 DI RAWA BANJIRAN SUNGAI KAMPAR KIRI, RIAU [Food habits of Thynnichtys thynnoides Bleeker, 1852 in floodplain river of Kampar Kiri, Riau] - Prawira Atmaja R.P. Tampubolon; Charles P.H. Simanjuntak (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2009)
Study on the food habits of Thynnichthys thynnoides in the floodplain of Kampar Kiri River, Riau, was conducted from July to Desember 2006, using experimental gillnet and trap. The main objectives of the study were to analyze the food compotition of T. thynnoides from two areas (Mentulik and Simalinyang) and the changes of the food in relation to season. Total samples are 252 fishes, comprises 125 fishes from Mentulik and 127 fishes from Simalinyang. Food analysis was determined by using Index of Preponderance. The result showed that the main food of T. thynnoides both in Mentulik and Simalinyang was Bacillariophyceae. At Mentulik, the most common prey items were Cocconeis, Cyclotella, and Nitzschia; on the other hand at Simalinyang Cocconeis, Cyclotella, and Pleurotaenium more representative. The composition of food items varied monthly, especially at Simalinyang. T. thynnoides from Mentulik and Simalinyang has same trophic positions.